Real effects of price stability with endogenous nominal indexation - Césaire Assah Meh; Vincenzo Quadrini; Yaz Terajima (Bank of Canada, 2009)
We study a model with repeated moral hazard where financial contracts are not fully indexed to inflation because nominal prices are observed with delay as in Jovanovic & Ueda (1997). More constrained firms sign contracts that are less indexed to the nominal price and, as a result, their investment is more sensitive to nominal price shocks. We also find that the overall degree of nominal indexation increases with the uncertainty of the price level. An implication of this is that economies with higher price-level uncertainty are less vulnerable to a price shock of a given magnitude, that is, aggregate investment and output respond to a lesser degree.
Keywords: E21; E31; E44; E52; 330; Economic models; Monetary policy framework; Financial markets; Transmission of monetary policy; Finanzmarkt; Moral Hazard; Indexierung; Preisniveaustabilität; Schock; Transmissionsmechanismus; Theorie